An updated list of Acanthocephalans (Acanthocephala) from animals in Vietnam - Ha, Nguyen Van (Academia Journal of Biology, 2016)
Acanthocephala is a phylum of parasitic worms characterized by the presence of an eversible proboscis, armed with spines, which is used to pierce and hold the gut wall of the host. In Vietnam, acanthocephalans have been studied about 50 years ago. In 1977, the first classification of the parasitic acanthocephalans, including 26 species of 10 genus, 5 families, 3 orders, from birds and mammals was published. This excluded acanthocephalans from fish. Recently, many other acanthocephans have been described from all classes of the vertebrates. In addition, the classification of acanthocephalans has been changed. This article updated the list of acanthocephalans from animals in Vietnam following the latest classification. To date, 72 species of 34 genus, 15 families, 8 orders of 3 classes (Archiacanthocephala, Eoacanthocephala and Palaeacanthocephala) were listed, consisting 13 from freshwater fishes, 21 from marine fishes, 3 from amphibians, from reptiles, 29 from birds and 5 from mammals. The list of acanthocephalans from animals in Vietnam with the  information of their hosts, distributions and references were given herein.